High utilization rate of vena cava filters in deep vein thrombosis - Jaff, Michael R.; Goldhaber, Samuel Z.; Tapson, Victor F. (Thrombosis and Haemostasis, 2005)
The objective was to investigate newly diagnosed patients with deep vein thrombosis (DVT) who received inferior vena cava filters (IVCFs). A prospective registry enrolled 5451 patients from 183 US study sites. In all patients, examination by venous duplex ultrasound confirmed the diagnosis of DVT. We collected and analyzed data on 781 patients who received an IVCF . The most frequently prescribed treatments were low–molecular-weight heparin and unfractionated heparin, which were used as a bridge to warfarin in 39% (n=2143) and 35% (n=1926) of patients, respectively. Of the total population, 781 (14%) (235 outpatients, 546 inpatients) underwent IVCF placement. The most common reasons for IVCF placement were contraindication to anticoagulation (n = 271), prophylaxis (n = 259), major bleeding related to anticoagulation therapy (n = 92), and anticoagulation failure (n = 73). Multivariate analysis revealed that patients were more likely to undergo IVCF insertion with multiple system organ failure (odds ratio [OR], 3.6; 95% CI, 1.48–8.60), previous stroke (OR, 3.2; 95% CI, 2.11–4.74), or history of pulmonary embolism (OR, 2.4; 95% CI, 1.95–2.91). In conclusion, a surprisingly high 14% (781) of patients with confirmed DVT received an IVCF. Many of these patients may have warranted less invasive methods of venous thromboembolism prophylaxis. Improved physician education regarding mechanical and pharmacologic prophylaxis alternatives might reduce the use of IVCFs.
Keywords: Deep vein thrombosis; pulmonary embolism; heparins / glycosaminoglycans; intravascular devices